Pengaruh Motivasi Dan Kompetensi SDM Terhadap Produktivitas Kerja Aparatur Desa Momunu Kabupaten Buol - ayuwandira morad; Sri Indah Wahyuni (Economy Deposit Journal (E-DJ), 2023)
There are still problems with the Momunu Village apparatus due to a lack of motivation and ability to work which causes decreased work productivity. This study aims to determine the effect of motivation and competence of human resources on the work productivity of Momunu Village apparatus, Momunu District, Buol Regency. This research uses quantitative research methods. The data source is primary data, namely data obtained through questionnaires, interviews and documentation related to this study and using multiple linear regression methods Based on the results of the study, it showed that the motivation variable partially had no effect on the work productivity variable, as evidenced by the results of the t test with a significance value of 0.087 above the value of 0.05. However, the human resource competence variable partially has a significant effect on work productivity variables with a significance value of 0.003 below the value of 0.05. Simultaneously motivation and competence of human resources have a significant effect on work productivity with a significance value of 0.000 above the value of 0.05.